The impact of LED lightning on the content of photosynthetic pigments in tomato leaves - T. V. Nikanovich; Yu. V. Trofimov; M. I. Barkun (Овощи России)
Relevance and methods. We studied the influence of LED lighting of different spectral composition on the content of photosynthetic pigments in tomato leaves to identify the most optimal lighting option suitable for obtaining high-quality seedlings under controlled conditions. We used LED lamps in which the ratio of the photon flux density (PFD) of the orange-red band (607–694 nm) to the PFD of the blue band (400–495 nm) varied from 1 to 20. In this case, the proportion of the PFD in the range 580-607 nm ( yellow) ranged from 13 to 22%, and the fraction of photons in the range 495–580 nm (green) ranged from 18 to 38%. The research was carried out with two varieties of Belarusian tomato varieties, which differed in a number of morphobiological characteristics.Results. It was found that the use of LED lighting of different spectral composition had mainly an inhibitory effect on the biosynthesis of chlorophylls and carotenoids in the leaf tissue of plants. The decrease in the amount of pigments, in comparison with the control variant, reached 47-57%. It was revealed that under all studied lighting options, with the exception of conditions where the spectral ratio R / B ("red/blue") was 0.8, the value of the total inhibitory effect in the Cherry Coral variety was 1.2-1.7 times lower than that of the Zorka variety, which indicated a significantly lower susceptibility of the pigment fund of the former to LED lighting. The smallest inhibitory effect of the latter on the biosynthesis of photosynthetic pigments in both tomato varieties was established at a photon flux of 69.1 μmol/s, while the greatest, exceeding it by 3.0-3.1 times in the Zorka variety and 4.5-5.3 times for the Cherry Coral variety with a photon flux of 73.9 μmol/s.